Trypanosoma cruzi alkaline 2-DE: Optimization and application to comparative proteome analysis of flagellate life stages - Magalhães, Adriana D (BioMed Central, 2008)
BACKGROUND: Trypanosoma cruzi, a flagellate protozoan, is the etiological agent of Chagas disease, a chronic illness that causes irreversible damage to heart and digestive tract in humans. Previous 2-DE analyses of T. cruzi proteome have not focused on basic proteins, possibly because of inherent difficulties for optimizing 2-DE in the alkaline pH range. However, T. cruzi wide pH range 2-DE gels have shown few visible spots in the alkaline region, indicating that the parasite either did not have an appreciable amount of alkaline proteins or that these proteins were underrepresented in the 2-DE gels. RESULTS: Different IEF conditions using 6–11 pH gradient strips were tested for separation of T. cruzi alkaline proteins. The optimized methodology described here was performed using anodic "paper bridge" sample loading supplemented by increased concentration of DTT and Triton X-100 on Multiphor II (GE Healthcare) equipment and an electrode pad embedded in DTT- containing solution near the cathode in order to avoid depletion of reducing agent during IEF. Landmark proteins were identified by peptide mass fingerprinting allowing the production of an epimastigote 2-DE map. Most identified proteins corresponded to metabolic enzymes, especially those related to amino acid metabolism. The optimized 2-DE protocol was applied in combination with the "two-in-one gel" method to verify the relative expression of the identified proteins between samples from epimastigote and trypomastigote life stages. CONCLUSION: High resolution 2-DE gels of T. cruzi life forms were achieved using the optimized methodology and a partial epimastigote alkaline 2-DE map was built. Among 700 protein spots detected, 422 were alkaline with a pI above 7.0. The "two-in-one gel" method simplified the comparative analysis between T. cruzi life stages since it minimized variations in spot migration and silver-stained spot volumes. The comparative data were in agreement with biological traits of T. cruzi life forms and also corroborated previous T. cruzi proteomic studies. For instance, enzymes related to amino acid metabolism and dehydrogenases were more abundant in epimastigote 2-DE gel whilst trans-sialidase and a paraflagellar protein were found specifically in the trypomastigote 2-DE profile.